A simple plan to address social security insolvency - Andrew G. Biggs; Kristin A. Shapiro (American Enterprise Institute (AEI), 2024)
Social Security's Old Age and Survivors Insurance trust fund is projected to be exhausted in 2033. Without intervening legislative action, current law dictates that benefits at that time would need to be reduced by approximately 21 percent. It is commonly assumed that such benefit reductions must be made on an equal percentage basis for every retiree, a step that would double the elderly poverty rate and reduce total income for the median senior household by almost 14 percent. However, when a federal program lacks sufficient funds, the executive branch in fact possesses considerable discretion to allocate those limited funds in a reasonable manner. This discretion would allow the President at the time of trust fund exhaustion to pay full Social Security benefits to those in greatest need. We present a framework in which monthly benefits in 2033 would be capped at 2,050 (in 2024 dollars), an amount that would provide full scheduled benefits for roughly half of retirees; benefit reductions for the remaining, higher-income, half of retirees would be progressive. This framework would prevent any increase in the elderly poverty rate due to Social Security's insolvency and approximately 80 percent of beneficiaries would receive a smaller benefit reduction than had every retiree been subjected to an across-the-board cut. In other words, even if Congress does nothing to address Social Security's insolvency between now and 2033, the worst effects of Social Security insolvency could be prevented by executive action. Because our framework could be implemented under existing law, it also provides a reasonable starting point for negotiations over long-term Social Security reforms.
Keywords: 330